A high-strength tear-resistant woven container bag and preparation method thereof
By adding polyethylene and modified filler to polypropylene and forming a crosslinking network, the problem of poor strength and tear resistance of container bags is solved, and higher strength and tear resistance are achieved.
Patent Information
- Application Number
- CN202211551230.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-05
AI Technical Summary
Existing container bags are prone to tearing or rupture when carrying load weight, and the filler distribution in the braided wire is uneven, resulting in poor strength and tear resistance.
Polyethylene, nano-calcium carbonate, talc powder, glass powder and other fillers are added to polypropylene, and the fillers are modified by modifiers to form a uniform skeleton structure and cross-linking network to enhance the strength and tear resistance of the braided wire.
It significantly improves the strength and tear resistance of the container bag, extends the service life, and by evenly distributing the filler, the aggregation of the filler is avoided and the overall performance of the braided wire is improved.
Smart Images

Figure GDA0005322259180000071 
Figure GDA0005322259180000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a high-strength tear-resistant woven container bag and a preparation method thereof. Background Art
[0002] Container bags are a kind of flexible transport packaging container, which are widely used for the transport packaging of powdered, granular and blocky items such as food, grains, medicines, chemicals and minerals. Container bags are usually made by weaving woven wire, and the material of the woven wire is usually high polymer materials such as polypropylene and polyethylene.
[0003] Since bulk bags need to bear a strong weight during use and are more prone to tearing or rupture, in order to improve the strength of the bulk bags, fillers are usually added directly to the woven wire base material. The fillers enhance the strength of the woven wire and reduce the possibility of tearing or rupture of the bulk bags.
[0004] With regard to the above-mentioned related technologies, simply adding fillers to the woven wire substrate will cause the fillers to agglomerate more easily in the woven wire substrate, resulting in poor uniformity of filler distribution in the woven wire, that is, poor strength of the woven wire. In addition, the woven wire is also more likely to age and break. Therefore, the container bag has the defects of poor strength and tear resistance. Summary of the invention
[0005] In order to improve the defects of poor strength and tear resistance of container bags, the present application provides a high-strength tear-resistant woven container bag and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-strength tear-resistant woven container bag, adopting the following technical solution: a high-strength tear-resistant woven container bag, comprising woven wires, the woven wires comprising the following materials in parts by weight: 10-20 parts of reinforcing masterbatch, 1-5 parts of polyethylene and 75-89 parts of polypropylene, the reinforcing masterbatch comprising a filler, the filler comprising at least one of nano-calcium carbonate, talcum powder, and glass micropowder, the reinforcing masterbatch also comprising waste rubber powder, the filler being a filler modified by a modifier, and the modifier being selected from any one of stearic acid, calcium stearate, borate, and chlorinated paraffin.
[0007] By adopting the above technical solution, the technical solution of the present application preferably adopts the addition of polyethylene to polypropylene. After the polyethylene is added, it can destroy part of the spherical crystals of polypropylene, form a fragmented structure, enhance the interaction force between the two-phase interface of polyethylene and polypropylene, and improve the tensile properties, toughness and strength of the braided yarn. At the same time, the amount of polyethylene added is optimized in the technical solution of the present application. The appropriate amount of polyethylene added can maintain excellent interfacial interaction force, is not easy to produce incompatibility or phase separation, and stably improves the strength of the braided yarn.
[0008] Secondly, the present application adopts any one of nano calcium carbonate, talcum powder, and glass powder, and through the filling of fine particles, a uniform skeleton structure can be formed in the braided silk substrate, and each component in the braided silk substrate is pulled, so as to play a diffusion enhancement effect in the braided silk substrate, and stably improve the strength and tear resistance of the braided silk. The filler is modified by stearic acid, calcium stearate, boric acid ester or chlorinated paraffin, and a chemical coupling layer, a hydrophobic layer or a lubricating layer can be formed on the surface of the filler, which effectively improves the compatibility between the filler and the braided silk substrate, reduces the possibility of filler agglomeration, and enables the braided silk substrate to obtain uniform strength.
[0009] Finally, the present application adopts the method of adding waste rubber powder to the braided silk base material. Since the waste rubber powder has a network structure with a high degree of cross-linking, the network structure is added to the braided silk base material, which cooperates with the filler to form a system in which the filler network and the cross-linked network cooperate with each other, and the strength of the braided silk base material is synergistically improved. In addition, the cross-linked network in the waste rubber powder can load the filler to a certain extent, further enhancing the coordination effect between the cross-linked network and the filler network.
[0010] Preferably, the waste rubber powder is nano-scale waste rubber powder.
[0011] By adopting the above technical solution, the particle size of the waste rubber powder is optimized in the technical solution of the present application, the nano-scale waste rubber powder has better dispersion uniformity in the woven wire substrate, and the network structure can evenly enhance the strength of the woven wire. The nano-scale waste rubber powder can play a role in heterogeneous nucleation, reduce the supercooling of polypropylene, shorten the half-crystallization time, and enhance the strength and tear resistance of the woven wire.
[0012] Preferably, the reinforcing masterbatch further comprises a compatibilizer, and the compatibilizer comprises a long-chain branched copolymer of polypropylene and polyethylene.
[0013] By adopting the above technical scheme, the long-chain branched copolymer of polypropylene and polyethylene is preferably used as a compatibilizer in the technical scheme of the present application. Polypropylene and polyethylene form a long-chain branched structure through a co-branching system. The long-chain branched structure can play a connecting role in the woven silk substrate, effectively promoting the compatibility of the reinforcing masterbatch with the woven silk substrate, and promoting the compatible bonding and uniform dispersion between the components of the woven silk, reducing the possibility of agglomeration of the filler in the woven silk substrate. The addition of the compatibilizer allows the woven silk substrate to have crystallization interactions and bonding compatibility, and the reinforcing masterbatch can be evenly dispersed in the woven silk substrate, effectively improving the strength, tensile effect and tear resistance of the woven silk.
[0014] Preferably, the compatibilizer further comprises a maleic anhydride grafted polypropylene compatibilizer or a polyethylene wax grafted with methyl methacrylate.
[0015] By adopting the above technical scheme, the technical scheme of the present application preferably adopts maleic anhydride grafted polypropylene compatibilizer as a compatibilizer, introduces anhydride polar groups into the woven silk substrate, improves the surface wettability of the filler, and improves the uniformity of the dispersion of the filler in the woven silk substrate; and the inactive chain segments in the compatibilizer can form a crystal bond with the polymer chain in the woven silk matrix, forming a strong interface bond, so that the woven silk obtains uniform strength and tear strength. The maleic anhydride grafted polypropylene compatibilizer can also connect with the surface active groups in the waste rubber powder, effectively improve the interface compatibility between the two, and further improve the strength of the woven silk.
[0016] In the technical solution of the present application, polyethylene wax grafted with methyl methacrylate is used as a compatibilizer. The polyethylene wax has a large polarity and a strong interaction force with the filler, thereby wrapping the filler and effectively reducing the possibility of agglomeration between the fillers, so that the filler can be evenly dispersed in the braided wire substrate, thereby obtaining uniform strength of the braided wire.
[0017] Preferably, the reinforcing masterbatch further comprises glass fiber and high melt polypropylene.
[0018] By adopting the above technical solution, firstly, in the technical solution of the present application, it is preferred to add glass fiber to the reinforcing masterbatch. The linear structure of the glass fiber can break through part of the agglomerated filler and improve the dispersion uniformity of the filler in the woven wire substrate.
[0019] Secondly, in the present application, glass fiber and high-melt polypropylene are used in combination. The high-melt polypropylene can properly wrap the glass fiber. When the reinforcing masterbatch is added to the woven wire substrate for melt mixing, the high flow rate of the high-melt polypropylene can improve the dispersion uniformity of the glass fiber in the woven wire substrate. In addition, during the molding process of the woven wire substrate, the high-melt polypropylene is easier to migrate toward the surface of the woven wire. The possibility of exposure of the glass fiber is reduced through wrapping and covering. The glass fiber can stably play a pulling and reinforcing role in the woven wire, thereby stably improving the strength of the woven bag.
[0020] Finally, high-melt polypropylene can also modify the waste rubber powder, which can effectively improve the interface compatibility between the waste rubber powder and the woven silk substrate, so that the network structure of the waste rubber powder is evenly dispersed in the woven silk substrate, further improving the strength of the woven silk.
[0021] Preferably, the addition amount of the high melt polypropylene is 3-5 parts by weight.
[0022] By adopting the above technical scheme, the addition amount of high-melt polypropylene is optimized in the technical scheme of the present application. The appropriate addition amount can promote the uniformity of dispersion of glass fibers between fiber substrates, reduce the frequency of tumbling and spinning of glass fibers in the woven wires, and the glass fibers can stably improve the strength of the woven wires.
[0023] Preferably, the filler also includes at least one of three-dimensional attapulgite or lamellar graphene.
[0024] By adopting the above technical solution, the present application preferably adopts the method of adding three-dimensional attapulgite to the filler. The flexible carbon chain in the three-dimensional attapulgite is more likely to curl, and the curled carbon chain structure is added to the braided wire substrate. During the process of stretching the braided wire, the curled carbon chain structure can stretch, which effectively improves the tensile properties and tear resistance of the braided wire. Secondly, the curled carbon chain structure can still break through the agglomeration between the fillers and appropriately load the fillers, thereby improving the uniformity of the dispersion of the fillers.
[0025] The present application adopts the method of adding flaky graphene to the filler. The flaky graphene has a better dispersion effect in the woven silk substrate. The flaky structure breaks through the agglomeration of the filler and loads the filler to form an intercalated structure. The filler can be evenly dispersed and the bonding strength between the flaky graphene and the woven silk substrate is enhanced.
[0026] Finally, the present application adopts a combination of flaky graphene and three-dimensional attapulgite, and the flaky structure is combined with a curled flexible carbon chain. The curled carbon chain is connected to the flaky structure, and adjacent flaky structures can be firmly combined through the curled carbon chain to form a cascade zipline system similar to bird feathers. In the process of the braided wire being torn, the curled carbon chain structure stably improves the tear resistance of the braided wire through deformation and mutual pulling.
[0027] Preferably, the graphene sheet is loaded with polyacrylonitrile filaments.
[0028] By adopting the above technical scheme, polyacrylonitrile precursor is loaded on the surface of the graphene sheet. Since the molecular chains or segments of the polyacrylonitrile precursor are in a curled state, the curled structure is directly grafted on the surface of the graphene sheet, and the mutually entangled curled structure is introduced into the fiber substrate to stably form a cascade zipline system similar to bird feathers, which effectively improves the tear resistance of the braided silk.
[0029] Preferably, the polyacrylonitrile precursor is also loaded with polyamide.
[0030] By adopting the above technical solution, polyamide is further loaded on the polyacrylonitrile precursor, so that the graphene flakes, polyacrylonitrile precursor and polyamide form a layered and enhanced rigid-flexible structure, which improves the anchoring sites and active sites on the polyacrylonitrile precursor, increases the mechanical interlocking between the curled structures, and stably improves the tear resistance of the braided wire. Secondly, the layered structure of the rigid-flexible structure can form a gradient modulus intermediate layer in the braided wire substrate, which plays a role in the transfer of fracture energy and further improves the strength of the braided wire.
[0031] In a second aspect, the present application provides a method for preparing a high-strength tear-resistant woven container bag, using the following technical solution:
[0032] A method for preparing a high-strength tear-resistant woven container bag comprises the following steps: taking polypropylene, polyethylene and reinforcing masterbatch respectively according to a formula, stirring and mixing, melt extruding to obtain a film, cutting and filamenting, stretching, heat setting, placing, laminating and sewing to prepare a container bag.
[0033] By adopting the above technical scheme, in the technical scheme of the present application, a container bag is prepared by stretching, shaping, laminating and other steps of the woven wire, which can effectively improve the strength and tear resistance of the container bag and extend the service life of the container bag.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. Since the present application adopts the method of adding polyethylene to polypropylene, the polyethylene can destroy part of the spherical crystals of polypropylene after being added to form a fragmented structure, which can enhance the interaction force between the two-phase interface of polyethylene and polypropylene, and improve the tensile properties, toughness and strength of the braided yarn.
[0036] By filling the fine particles in the filler, a uniform skeleton structure is formed in the braided silk substrate, and each component in the braided silk substrate is pulled, which has a dispersion enhancement effect in the braided silk substrate. The filler is modified with stearic acid, calcium stearate, boric acid ester or chlorinated paraffin to form a chemical coupling layer, a hydrophobic layer or a lubricating layer on the surface of the filler, which effectively improves the compatibility between the filler and the braided silk substrate, reduces the possibility of filler agglomeration, and enables the braided silk substrate to obtain uniform strength.
[0037] Adding waste rubber powder to the braided silk base material, because the waste rubber powder has a network structure with a high degree of cross-linking, adding a network structure to the braided silk base material cooperates with the filler, and the filler network and the cross-linked network cooperate with each other to synergistically improve the strength of the braided silk base material. In addition, the cross-linked network in the waste rubber powder can load the filler to a certain extent, further enhancing the coordination effect between the cross-linked network and the filler network.
[0038] 2. In the present application, it is preferred to use glass fiber and high-melt polypropylene in combination. High-melt polypropylene can properly wrap the glass fiber. When the reinforcing masterbatch is added to the woven wire substrate for melt mixing, the high flow rate of high-melt polypropylene can improve the dispersion uniformity of the glass fiber in the woven wire substrate. In addition, during the molding process of the woven wire substrate, high-melt polypropylene can easily migrate toward the surface of the woven wire, thereby reducing the possibility of exposure of the glass fiber through wrapping and covering. The glass fiber can be stably in the woven wire to play a pulling and reinforcing role.
[0039] High-melt polypropylene can also modify the waste rubber powder, effectively improving the interface compatibility between the waste rubber powder and the woven silk substrate, so that the network structure of the waste rubber powder is evenly dispersed in the woven silk substrate, further improving the strength of the woven silk.
[0040] 3. In the present application, flaky graphene is combined with three-dimensional attapulgite, and the flaky structure is combined with a curled flexible carbon chain. The curled carbon chain is connected to the flaky structure, and adjacent flaky structures can be firmly combined through the curled carbon chain to form a cascade zipline system similar to bird feathers. In the process of the braided wire being torn, the curled carbon chain structure stably improves the tear resistance of the braided wire through deformation and mutual pulling.
[0041] 4. In this application, a layered reinforced rigid-flexible structure is formed by using graphene sheets, polyacrylonitrile precursor and polyamide, which improves the anchoring sites and active sites on the polyacrylonitrile precursor, increases the mechanical interlocking between the curled structures, and stably improves the tear resistance of the braided wire. Secondly, the layered structure of the rigid-flexible structure can form a gradient modulus intermediate layer in the braided wire substrate, which plays a role in fracture energy transfer and further improves the strength of the braided wire. DETAILED DESCRIPTION
[0042] The present application is further described in detail below in conjunction with embodiments.
[0043] Preparation Example
[0044] Preparation example of long chain branched copolymer of polypropylene and polyethylene
[0045] Preparation Example 1
[0046] Take 0.01kg of diisopropylbenzene peroxide (DCP) and 0.12kg of trimethylolpropane triacrylate (TMPTA) and dissolve them in acetone, spray them on 5kg of high molecular weight polyethylene and 5kg of isotactic polypropylene, add 0.01kg of zinc dimethyldithiocarbamate, and completely volatilize the acetone in a fume hood. Put it into a torque rheometer for internal mixing at a rotor speed of 85r / min and 200°C. Cool and crush to obtain a long-chain branched copolymer of polypropylene and polyethylene.
[0047] Preparation Example of Maleic Anhydride Grafted Polypropylene Compatibilizer
[0048] Preparation Example 2
[0049] 1 kg of high melt polypropylene (MF 650Y), 2 g of DCP and 12 g of maleic anhydride were melt-grafted, co-extruded and granulated to prepare a maleic anhydride grafted polypropylene compatibilizer.
[0050] Preparation Example of Polyethylene Wax Grafted with Methyl Methacrylate
[0051] Preparation Example 3
[0052] Take 1kg of methyl methacrylate, 0.5kg of toluene and 0.01kg of DCP, mix evenly, add 10kg of polyethylene wax, mix evenly, place at 80℃ for 24h, vacuum dry at 100℃, keep at normal pressure for 5h, evacuate to -0.01MPa, keep for 12h, take out, and obtain grafted with methyl methacrylate.
[0053] Compatibilizer Preparation Example
[0054] Preparation Example 4
[0055] A long-chain branched copolymer of polypropylene and polyethylene is used as the compatibilizer 1.
[0056] Preparation Example 5
[0057] 2 kg of long-chain branched copolymer of polypropylene and polyethylene and 1 kg of maleic anhydride grafted polypropylene compatibilizer were mixed as compatibilizer 2.
[0058] Preparation Example 6
[0059] 2 kg of a long-chain branched copolymer of polypropylene and polyethylene and 1 kg of polyethylene wax grafted with methyl methacrylate were taken and mixed as the compatibilizer 3.
[0060] Example of preparing graphene sheets
[0061] Preparation Example 7
[0062] 2 g of graphene oxide (lamellar structure) was mixed with 800 mL of DMF and ultrasonically treated for 8 h, heated to 70°C and maintained for 30 min, 4 g of reduced polyacrylonitrile precursor and 0.3 mL of sulfuric acid were added, refluxed at 70°C for 12 h, taken out, rinsed with DMF and ethanol, and lamellar graphene grafted with polyacrylonitrile precursor was obtained as graphene 1.
[0063] Preparation method of reduced polyacrylonitrile precursor: place the polyacrylonitrile precursor in DMF, add 1g of lithium aluminum hydride, reflux and stir at 70°C for 2h, then slowly add 200mL of 2.0N hydrochloric acid solution, wash with water until the washing liquid is neutral, and obtain epoxy polyacrylonitrile precursor.
[0064] Preparation Example 8
[0065] Take 0.4g of graphene sheets grafted with polyacrylonitrile precursor and immerse it in toluene solution, add 6.65mL of adipoyl chloride, reflux at 100℃ for 2h under nitrogen protection, add 5.56g of caprolactam and continue to react for 4h to obtain an intermediate, wash and dry. Heat 80g of caprolactam to 120℃ at 0.1MPa to melt, punch until there are no bubbles, add 0.24g of sodium hydroxide, continue to evacuate until there are no bubbles, raise the temperature to 140℃ and keep for 30min, add the intermediate, raise the temperature to 150℃ within 30min, continue stirring for 24h, take out, wash alternately with formic acid and deionized water, wash 3 times each, and obtain graphene sheets grafted with polyacrylonitrile precursor and PA as graphene 2.
[0066] Example
[0067] Examples 1-3
[0068] On the one hand, the present application provides a high-strength tear-resistant woven container bag, which is woven from woven yarns, and the woven yarns contain reinforcing masterbatch, polyethylene and polypropylene, and the mass is shown in Table 1. The reinforcing masterbatch includes a filler, and in this embodiment, the filler is glass powder, and the reinforcing masterbatch also includes waste gas abandoned rubber powder, and the glass powder is glass powder modified by borate, that is, the reinforcing masterbatch includes waste rubber powder and glass powder in equal mass ratios.
[0069] It is worth noting that the filler includes but is not limited to: any one or more of nano calcium carbonate, talcum powder, and glass powder. In this embodiment, glass powder is selected;
[0070] The filler is a filler modified by a modifier, and the modifier includes but is not limited to: any one or more of stearic acid, calcium stearate, boric acid ester, and chlorinated paraffin. In this embodiment, boric acid ester is selected.
[0071] Modification treatment: the glass powder is dried, and then the glass powder and borate solution (a mixture of 40% borate and 60% ethanol) are stirred and mixed, and the mixture is discharged to obtain the modified glass powder.
[0072] On the other hand, the present application provides a method for preparing a high-strength tear-resistant woven container bag, comprising the following steps: taking polypropylene, polyethylene and reinforcing masterbatch respectively, stirring and mixing, melt-extruding to obtain a film, cutting and making wires to obtain woven wires 1-3, and then stretching, heat-setting, placing, laminating, and sewing to prepare container bags 1-3.
[0073] Table 1 Composition of braided yarns in Examples 1-3
[0074]
[0075] Example 4
[0076] The difference from Example 2 is that the waste rubber powder is nano-scale waste rubber powder, and the woven wire 4 and the woven bag 4 are prepared.
[0077] Embodiment 5-7
[0078] The difference from Example 2 is that the reinforcing masterbatch includes 3 kg of waste rubber powder, 13 kg of glass powder and 1 kg of compatibilizer 1-3, and woven wires 5-7 and woven bags 5-7 are prepared.
[0079] Example 8
[0080] The difference from Example 2 is that the reinforcing masterbatch includes 3 kg of waste rubber powder, 11 kg of glass powder, 1 kg of glass fiber and 2 kg of high-melt polypropylene to prepare woven wires 8 and woven bags 8.
[0081] Example 9
[0082] The difference from Example 5 is that the reinforcing masterbatch includes 3 kg of waste rubber powder, 10 kg of glass powder, 1 kg of compatibilizer 2, 1 kg of glass fiber and 2 kg of high-melt polypropylene to prepare woven wires 9 and woven bags 9.
[0083] Example 10
[0084] The difference from Example 2 is that the filler further includes three-dimensional attapulgite, that is, the reinforcing masterbatch includes 3kg of waste rubber powder, 13kg of glass powder and 1kg of three-dimensional attapulgite, and the woven wire 10 and the woven bag 10 are prepared.
[0085] Embodiment 11
[0086] The difference from Example 2 is that the filler also includes flake graphene, that is, the reinforcing masterbatch includes 3kg of waste rubber powder, 13kg of glass powder and 1kg of flake graphene, and the woven wire 11 and the woven bag 11 are prepared.
[0087] Example 12
[0088] The difference from Example 2 is that the filler also includes lamellar graphene and three-dimensional attapulgite, that is, the reinforcing masterbatch includes 3kg of waste rubber powder, 13kg of glass powder, 0.5kg of three-dimensional attapulgite and 0.5kg of lamellar graphene, to prepare woven wire 12 and woven bag 12.
[0089] Example 13
[0090] The difference from Example 12 is that the graphene flakes are loaded with polyacrylonitrile precursor, that is, an equal mass of graphene 1 is used to replace the graphene flakes in Example 12 to prepare the woven yarn 13 and the woven bag 13.
[0091] Embodiment 14
[0092] The difference from Example 12 is that an equal mass of graphene 2 is used to replace the flake graphene in Example 12 to prepare the woven wire 14 and the woven bag 14.
[0093] Embodiment 15
[0094] The difference from Example 9 is that the reinforcing masterbatch includes 3kg of waste rubber powder, 9kg of glass powder, 1kg of expander 2, 1kg of glass fiber, 0.5kg of three-dimensional attapulgite and 0.5kg of graphene 2 and 2kg of high-melt polypropylene to prepare woven wire 15 and woven bag 15.
[0095] Comparative Example
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 2 is that in this comparative example, no waste rubber powder is added to prepare the woven yarn 16 and the woven bag 16.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 2 is that in this comparative example, no polyethylene is added to prepare the woven wire 17 and the woven bag 17 .
[0100] Performance testing
[0101] (1) Tensile properties test: The test shall be conducted in accordance with GB / T 1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for films and sheets.
[0102] (2) Adhesion performance test: Test the tear resistance according to "QB / T1130-1991 Plastic Right Angle Tear Performance Test Method";
[0103] Table 2 Performance test
[0104]
[0105] Combining the performance test comparison in Table 2, we can find that:
[0106] (1) By comparing Examples 1-3, Example 4, and Comparative Example 1-2, it can be found that the tensile properties and tear resistance of the braided silk obtained in Examples 1-4 are improved, which shows that the addition of polyethylene in this application destroys part of the spherical crystals of polypropylene, enhances the interaction force between the two-phase interface of polyethylene and polypropylene, and improves the mechanical properties of the braided silk; optimizes the addition amount of each component to maintain excellent interfacial force; through the modification of the filler by the modifier, a chemical coupling layer, a hydrophobic layer or a lubricating layer is formed on the surface of the filler, which effectively improves the compatibility between the filler and the braided silk substrate, so that the braided silk obtains uniform strength. Through the cross-linked network structure in the waste rubber powder, a system of the filler network and the cross-linked network that cooperate with each other is formed, and the nano-scale waste rubber powder can play a role of heterogeneous nucleation, synergistically improving the strength of the braided silk substrate.
[0107] (2) By comparing Examples 5-7 with Example 2, it can be found that the tensile properties and tear resistance of the braided silk prepared in Examples 5-7 are improved. This shows that the present application adopts the method of adding a compatibilizer to the braided silk substrate, introducing polar groups, wetting the filler surface, etc., thereby hindering the possibility of agglomeration between fillers, improving the compatibility between the components in the braided silk, and obtaining uniform strength of the braided silk.
[0108] (3) By comparing Examples 8-9 with Example 2, it can be found that the tensile properties and tear resistance of the braided wires prepared in Examples 8-9 are improved, which shows that the application adopts the addition of fiber structure to form a pulling structure to enhance the strength of the braided wire; the high flow rate of high-melt polypropylene improves the dispersion uniformity of glass fiber. During the braided wire substrate molding process, high-melt polypropylene is easier to migrate toward the surface of the braided wire, and the exposure of glass fiber is reduced by wrapping and covering. The glass fiber is stable in the braided wire to play a pulling and strengthening role. In addition, high-melt polypropylene can also modify the waste rubber powder, improve the interface compatibility of the waste rubber powder, and improve the compatibility between the components of the braided wire.
[0109] (4) By comparing Examples 10-12, Examples 13-15 and Example 2, it can be found that the tensile properties and tear resistance of the braided silk prepared in Examples 10-15 are improved, which shows that the present application adopts a combination of lamellar graphene and three-dimensional attapulgite, and the lamellar structure is combined with a curled flexible carbon chain. The lamellar structure is connected with a curled carbon chain, and adjacent lamellar structures can be firmly combined through the curled carbon chain to form a cascade zipline system similar to bird feathers. In the process of the braided silk being torn, the curled carbon chain structure is deformed and pulled by each other, thereby stably improving the tear resistance of the braided silk.
[0110] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength tear-resistant woven container bag, characterized in that: The invention comprises braided wires, which comprise the following materials in parts by weight: 10-20 parts of reinforcing masterbatch, 1-5 parts of polyethylene and 75-89 parts of polypropylene. The reinforcing masterbatch comprises fillers and waste rubber powder. The fillers are glass powders. The fillers also comprise three-dimensional attapulgite and flaky graphene. The flaky graphene is loaded with polyacrylonitrile precursor wires.
2. A high-strength tear-resistant woven container bag according to claim 1, characterized in that: The waste rubber powder is nano-scale waste rubber powder.
3. The high-strength tear-resistant woven container bag according to claim 1, characterized in that: The reinforcing masterbatch further comprises a compatibilizer, and the compatibilizer comprises a long-chain branched copolymer of polypropylene and polyethylene.
4. The high-strength tear-resistant woven container bag according to claim 3, characterized in that: The compatibilizer also includes a maleic anhydride grafted polypropylene compatibilizer or a polyethylene wax grafted with methyl methacrylate.
5. The high-strength tear-resistant woven container bag according to claim 1, characterized in that: The reinforcing masterbatch further comprises glass fiber and high melt polypropylene.
6. The high-strength tear-resistant woven container bag according to claim 5, characterized in that: The addition amount of the high melt polypropylene is 3-5 parts by weight.
7. The high-strength tear-resistant woven container bag according to claim 1, characterized in that: The polyacrylonitrile precursor is also loaded with polyamide.
8. A method for preparing a high-strength tear-resistant woven container bag according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: taking polypropylene, polyethylene and reinforcing masterbatch respectively according to the formula, stirring and mixing, melt extruding to obtain film, cutting and filament making, stretching, heat setting, placing, laminating and sewing to prepare container bags.
Citation Information
Patent Citations
ATP (attapulgite) intercalation modified graphene and UHMWPE (ultra-high-molecular-weight polyethylene) composite fiber and preparation method thereof
CN106012078A
Method for compatibilizing polypropylene / polyethylene blend
CN113024737A
Weaving material and preparation method thereof
CN113150444A
Polyethylene plastic woven yarn material for woven bag and preparation process thereof
CN113832563A